Nuzul Al-Qur’an dan Asbab Al-Nuzul: (Sebuah Metodologis dalam Memahami Al-Qur’an) - Inan Tihul (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2022)
The use of the term Al-Qur'an was "sent down" by Allah SWT to the Prophet Muhammad SAW., there is a big suspicion because of two things. First, maybe because Allah as the source of revelation is high even the Most High, while those other than Allah including the Prophet Muhammad are low compared to Allah. Second, it is also possible to remember that the angel Gabriel who conveyed the Qur'an to the Prophet Muhammad SAW descended from the sky, in this case the spirit realm. While the Prophet Muhammad and moreover other humans generally are as below. The Qur'an that Allah sent down does not entirely contain nuzul causes. Because the Al-Qur'an itself already existed and was complete in Lawh al-Mahfuzh before it was brought by the Angel Gabriel and delivered to the Prophet Muhammad. Asbab al-nuzul is only a case that will explain a verse. So the Al-Qur'an will continue to descend because of the will of Allah SWT even without any cause because the Al-Qur'an as its function is as a guide for the masses both at the time of the Prophet SAW and in the future.